Fatoriais fixos desbalanceados: Uma análise mal compreendida - Wechsler, Francisco Stefano [UNESP] (My University, 1998)
Few users of statistical packages are capable of analyzing unbalanced factorials properly, because introductory textbooks do not discuss this topic in detail. The present article is directed to agriculture researchers, with the purpose of clarifying the differences among several widely used programs. It shows how to test useful hypotheses about population means in models having qualitative and quantitative factors. The paper emphasizes the pitfalls of blindly applying packages without prior knowledge of the hypotheses being tested.

Poucos são os usuários de aplicativos estatísticos que sabem analisar adequadamente fatoriais desbalanceados, pois os compêndios introdutórios não tratam do assunto em detalhe. Este trabalho visa a explanar a pesquisadores de ciências agrárias as diferenças entre os principais programas. Mostra-se como testar hipóteses de interesse relativas a médias populacionais, em modelos com fatores qualitativos e quantitativos. Enfatizam-se os perigos de empregar cegamente os aplicativos sem antes conhecer as hipóteses por eles testadas.
Unbalanced factorials: A misunderstood analysis
Keywords: Missing data; Statistical analysis; Statistical packages